2017
DOI: 10.1038/s41598-017-05489-5
|View full text |Cite
|
Sign up to set email alerts
|

The cancer-associated cell migration protein TSPAN1 is under control of androgens and its upregulation increases prostate cancer cell migration

Abstract: Cell migration drives cell invasion and metastatic progression in prostate cancer and is a major cause of mortality and morbidity. However the mechanisms driving cell migration in prostate cancer patients are not fully understood. We previously identified the cancer-associated cell migration protein Tetraspanin 1 (TSPAN1) as a clinically relevant androgen regulated target in prostate cancer. Here we find that TSPAN1 is acutely induced by androgens, and is significantly upregulated in prostate cancer relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 85 publications
2
30
0
Order By: Relevance
“…Thus, TSPAN1 expression was detected in~45% (IHC) of laryngeal and pharyngeal tumors, a similar percentage to the upregulation of TSPAN1 detected at mRNA level (8 out of 16 patients) and also by Western blot (eight out of 12 patients). In good agreement, the overexpression of TSPAN1 in human cancer vs. adjacent non-cancerous tissue has been widely documented in cholangiocarcinoma [31,47,48], skin squamous cell carcinoma [36,49], esophageal carcinoma [34], ovarian carcinomas [50], prostate cancer [26], pancreatic cancer [35,37] and gastric carcinoma [51,52]. Moreover, TSPAN1 expression has been associated with HPV infection in cervical carcinomas, and considered an important diagnostic and prognostic marker, as strong TSPAN1 expression was found in a subset of high-grade cervical cancers and in most of the undifferentiated squamous cell carcinomas [53][54][55].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Thus, TSPAN1 expression was detected in~45% (IHC) of laryngeal and pharyngeal tumors, a similar percentage to the upregulation of TSPAN1 detected at mRNA level (8 out of 16 patients) and also by Western blot (eight out of 12 patients). In good agreement, the overexpression of TSPAN1 in human cancer vs. adjacent non-cancerous tissue has been widely documented in cholangiocarcinoma [31,47,48], skin squamous cell carcinoma [36,49], esophageal carcinoma [34], ovarian carcinomas [50], prostate cancer [26], pancreatic cancer [35,37] and gastric carcinoma [51,52]. Moreover, TSPAN1 expression has been associated with HPV infection in cervical carcinomas, and considered an important diagnostic and prognostic marker, as strong TSPAN1 expression was found in a subset of high-grade cervical cancers and in most of the undifferentiated squamous cell carcinomas [53][54][55].…”
Section: Discussionmentioning
confidence: 55%
“…TSPAN1 protein expression in tumors exhibited cytoplasmic and nuclear patterns that were separately scored, whereas TSPAN1 expression was negligible in matched adjacent normal epithelia and stromal cells ( Figure 6B). Although the cytoplasmic expression of TSPAN1 has been reported, we have not found previous works describing nuclear expression [26,31,33]. Forty-eight (45.2%) out of 106 patients showed cytoplasmic TSPAN1, and 34 of them showed concomitant cytoplasmic and nuclear staining (32.1% of total) ( Figure 6C).…”
Section: Tspan1 Expression In Patient Samples Correlations With Actimentioning
confidence: 70%
See 1 more Smart Citation
“…Cancer of the prostate is the most common type of cancer in the USA and was the second leading cause of cancer-associated mortality in 2016 (1). Uncontrolled growth associated with cellular migration and metastasis is the leading cause of cancer-associated mortality (2), with 17–34% of patients exhibiting metastatic disease at the time of initial diagnosis (3). Late-stage diagnosis remains an important problem, accounting for 37–43% of all cases, and is a significant risk factor for disease-associated mortality.…”
Section: Introductionmentioning
confidence: 99%
“…27 However, it is observed opposite effect that TSPAN1 control cell migration in prostate cancer. 21,28 These reports confirmed that TSPAN1 participate cell migration and invasion in some human cancer, meantime, indicating TSPAN1 may be involved in complex signalling pathway and dependent-tissue specificity. Epithelial-to-mesenchymal transition was considered to be a mechanism of epithelial cells' transformation in IPF.…”
Section: Discussionmentioning
confidence: 60%